2018
DOI: 10.1002/jcad.12219
|View full text |Cite
|
Sign up to set email alerts
|

Examining Leadership With American Counseling Association Presidents: A Grounded Theory of Leadership Identity Development

Abstract: In a grounded theory study, the authors examined the leadership identity development of 12 past presidents of the American Counseling Association. Using individual interviews, the authors identified 3 interactional themes that form a theoretical framework for leadership identity development: (a) influence, motivation, and support to lead; (b) leadership skills; and (c) reinforcing experiences. Implications for counselors and counselor educators are offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…This study provides additional support for the developmental nature of counseling leadership (Gibson et al, 2018;Luke & Goodrich, 2010;Storlie & Wood, 2014), as the participants framed their SJCRCL as developmental and cyclical. With that, the participants also indirectly challenged our current understanding of development within leadership, as they considered multiple aspects of development, rather than attributing development to one characteristic or opportunity.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This study provides additional support for the developmental nature of counseling leadership (Gibson et al, 2018;Luke & Goodrich, 2010;Storlie & Wood, 2014), as the participants framed their SJCRCL as developmental and cyclical. With that, the participants also indirectly challenged our current understanding of development within leadership, as they considered multiple aspects of development, rather than attributing development to one characteristic or opportunity.…”
Section: Discussionmentioning
confidence: 71%
“…Because we sought to understand counseling and counseling psychology leaders’ SJCRCL experiences and processes in the context of counseling associations and higher education, we sampled associate and full professors employed in higher education settings, who were a homogeneous population in terms of the identified research participation criteria, with moderately diverse social locations (Gibson et al, 2018; Hargons et al, 2017). Following institutional review board approval, purposive and snowball sampling was used to intentionally identify individuals who met the criteria for the study: (a) 18 years of age or older; (b) awarded a PhD or EdD; (c) served as an associate or full professor within the last five years; and (d) served in counseling association leadership within the past five years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This documented growth is arguably timely, given the increased emphasis on preparing professional counselors across all specialties to serve as a leader, whether that be in a counseling and supervisory relationship, community, or the counseling profession (Chang et al, 2012;Storlie et al, 2019). To date, the developing body of literature on counseling leadership has addressed theory, context, development, and actions of counseling leadership foci (Chang et al, 2012;Gibson, 2016;Gibson et al, 2018;McKibben et al, 2017b;Peters et al, in press;Peters et al, 2018;Storlie et al, 2015;Wahesh & Myers, 2014).…”
Section: Supervision As the Signature Pedagogy For Counseling Leadershipmentioning
confidence: 99%
“…Hill and Friedman (2019) suggested that counseling leadership development is "contingent on a robust and comprehensive interaction with the profession of counselor education" (p. 174). Scholars have identified professional role socialization, mentoring, service learning, emerging leader programming, and apprenticeship models as pathways for counseling leadership development (Gibson, 2016;Gibson et al, 2018;Lockard et al, 2014;Storlie et al, 2015;Peters et al, in press). Reflecting the importance of leadership as part of counselor professional identity, Lanning (1986) extended the discrimination model to include this as a fourth foci area for professional behavior, without much uptake over the past 25 years.…”
Section: Leadership Developmentmentioning
confidence: 99%